Frontiers in electronics selected papers from the Workshop on Frontiers in Electronics 2013 (WOFE-13), San Juan, Puerto Rico, 17-20 December 2013 - Christoloveanu, Sorin; Shur, Michael (Selected topics in electronics and systems, 2014)
This book brings together 11 invited papers from the Workshop on Frontiers in Electronics (WOFE) 2013 that took place at San Juan, Puerto Rico, in December 2013